Islam Lokal, Diskriminasi dan Representasinya dalam Dunia Digital - Ahmad Muttaqin (Jurnal Penelitian Agama, 2021)
Common discrimination is done by the majority Group against minorities. The majority group with the number and composition of more members feels the authority in a certain field so that they claim to do an action directed to the minority. The authority is constructed with a predominantly-minority dichotomistic mechanism aimed at maintaining power through the practice of domination. Minority groups will be difficult out of the practice of domination because of the available space in a dichotomist mechanism only exchanges positions. For minority groups, the exchange of positions is impossible because it uses quantity logic where the opportunity has been closed with a series of liberalization and bad stereotypes for example with distorted, perverted, and nyeleneh terminology. Local Islam has a relatively similar position to other minority groups. He was subjected to discrimination from the dominant group commonly portrayed by the mainstream community and religious institutions that identified as the majority. The social space that may be enabled to publish institutions and activities is limited so the information available is inadequate. The continuing implications are misunderstandings or even justifications that encourage collective discrimination. This situation became difficult for local Islamist groups who eventually chose to be passive, stagnant, and without a vast activity. The presence of the digital world changes the configuration of relations between local Islamist groups and external parties as well as shifting the base of authority to the base of discriminatory actions. This article will answer 2 (two) main questions of the first local Islamic response as a minority group against the proliferation of digital media that offers a new world that is more open and egalitarian. The social connection in this new world is formed not by an authority that is based on a majority-minority but technically-technologically dichotomistic mechanism. Second, the Solutive Digital world bid for local Islamist groups to parse the issue of sub domination. Social existence as an anti-thesis discrimination treatment is built with the basic principles of fast-paced, economical, and accessible digital media which it can only be met with productivity generating information up to date. Keywords: majority, minority, discrimination, local Islam, digital world.